Fulminant Idiopathic Intracranial Hypertension and Venous Stasis Retinopathy Resulting in Severe Bilateral Visual Impairment. Issue 2 (March 2017) - Voldman, Alexander; Durbin, Breanna; Nguyen, John; Ellis, Brian; Leys, Monique
Purpose: To report a complicated case of fulminant idiopathic intracranial hypertension and concomitant venous stasis retinopathy leading to postpapilledema optic atrophy. Methods: Case report. Results: A 34-year-old morbidly obese woman with a history of idiopathic intracranial hypertension (IIH) presented with a 1-month history of bilateral vision loss, diplopia, and left eye pain after being lost to follow-up for 6 years. Fundus examination revealed florid papilledema with venous tortuosity bilaterally. Brain and orbit magnetic resonance imaging showed bilateral globe flattening, intraocular optic nerve swelling in both eyes, and no abnormality on magnetic resonance venography. After additional workup including lumbar puncture with an opening pressure of 55 cm H2 O, a diagnosis of IIH was confirmed. Medical treatment with oral carbonic anhydrase inhibitors was initiated, followed by same-day bilateral optic nerve sheath decompression and ventriculoperitoneal shunt placement the following week. Fundus examination 2 months later revealed a persistent blood and thunder fundus suggestive of bilateral central retinal vein occlusions. Over the course of 6 months, both eyes displayed postpapilledema optic atrophy with light perception and hand motion vision in the right and left eyes, respectively. On Goldmann perimetry, the patient had vague limited isolated responses in both eyes to the largest target. Conclusions: Fulminant IIH can present with profoundly blinding complications recalcitrant to aggressive medical and surgical intervention. Central retinal vein occlusion is an uncommon blinding complication of IIH.